2022
DOI: 10.1017/erm.2022.19
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of FNDC5/irisin in various liver diseases: awakening the sleeping beauties

Abstract: Fibronectin type III domain-containing protein 5 (FNDC5) is a transmembrane protein and the precursor of irisin, which serves as a systemic exerkine/myokine with multiple origins. Since its discovery in 2012, this hormone-like polypeptide has rapidly evolved to a component significantly involved in a gamut of metabolic dysregulations and various liver diseases. After a decade of extensive investigation on FNDC5/irisin, we are still surrounded by lots of open questions regarding its diagnostic and therapeutic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…It has been reported that irisin plays important roles in regulating energy metabolism, insulin resistance, oxidative stress, inflammation, cell apoptosis, and fibrosis [ 26 , 27 , 28 ]. FNDC5/irisin is involved in different types of liver diseases, such as NAFLD, multiple detrimental insults-induced liver injury, and hepatic malignancy [ 29 ]. However, little is known about the effect of irisin on MI-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that irisin plays important roles in regulating energy metabolism, insulin resistance, oxidative stress, inflammation, cell apoptosis, and fibrosis [ 26 , 27 , 28 ]. FNDC5/irisin is involved in different types of liver diseases, such as NAFLD, multiple detrimental insults-induced liver injury, and hepatic malignancy [ 29 ]. However, little is known about the effect of irisin on MI-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…This is linked with the necessity of identifying the causes leading to the excessive accumulation of lipids in the liver. An increasing number of studies have indicated an etiological relationship between NAFLD and irisin concentration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%